KONSEP PENYANDIAN FILE JPEG DENGAN MENGGUNAKAN METODE LSB - Haikal Nando Winata; Raja Nasrul Fuad (Universitas Islam Sumatera Utara, 2017)
Steganography is a technique to hide text or messages that other people do not know the contents of the text or the secret message. Steganography technique is often used to avoid suspicion and to avoid other people desire to know the contents of the text or the secret message. Digital image is one of the most well-known media and the public by the author. Digital image acts as a medium or a text container you want to hide a secret message. Methods LSB (Least Significant Bit) that hides the bytes of text or message you want to hide into the last byte in the digital image. LSB method has the advantage of not changing the size and shape of the digital image by naked eye, text data or messages hidden can be restored without any change in size and shape